REPRESENTATION OF LITERARY TOURISM IN TEXT STUDY AND THE TOMB CAVE OF SITTI NURBAYA - I Nyoman Suaka (Prosiding Seminar Nasional dan Internasional HISKI, 2020)
The purpose of this paper is to describe the text of the novel Sitti Nurbaya by MarahRusli is associated with a grave and Sitti Nurbaya soap opera. The linkage of these three variables in the literary tourism frame (literary tourism) is a new approach in the study of literature. The literary tourism approach which is now looking for that form departs from the approach of literary sociology, literary psychology, literary anthropology and others that have been established as literary theories. In this analysis, an intertextuality approach will be used. Data were collected through observation of novel texts, SittiNurbaya soap operas and direct observations to the SittiNurbaya tomb cave located on the summit of Mount Padang, West Sumatra. Data was also obtained from interviews with officers and visitors of the SittiNurbaya Park attraction. Data analysis is intertext data analysis by juxtaposing novel texts, soap operas and the existence of SittiNurbaya’s grave cave. The results showed that the story of the Sitti Nurbaya novel became its own charm in the development of tourism in the city of Padang, West Sumatra. The SittiNurbaya tomb cave is part of Taman Sitti Nurbaya which is created with domestic and foreign tourists on certain days. As a legendary story, the Sitti Nurbaya story is believed by the local community to have occurred, even though Marah Rusli’s creation is fictional. The Sitti Nurbaya Park was used as the location for the Sitti Nurbaya soap opera played by Novia Kolopaking as Sitti Nurbaya, Gusti Randa as Samsul Bahri, HM Damsyik as Datuk Maringgih and other famous artists. Even the new bridge that was built towards the Mount Padang hill was named the Sitti Nurbaya Bridge. Thus the study of novel texts, grave caves and Sitti Nurbaya soap operas supports the concept and approach of literary tourism (literary tourism).